Perkembangan Industri 5.0 Terhadap Perekonomian Indonesia - Tangkas Ageng Nugroho; Achmad Kaisi Amarco; Muhammad Yasin (Pusat Riset dan Inovasi Nasional, 2023)
This research discusses the development of industry 5.0 and its impact on the Indonesian economy. Industry 5.0 is a concept that integrates artificial intelligence, robotics, automation, Internet of Things (IoT), and other technologies to create more efficient and connected production systems. This study aims to analyze how the implementation of Industry 5.0 has affected Indonesia's economic sector and the challenges faced in adopting this technology. A comprehensive literature review was conducted to understand the global developments of Industry 5.0 and then applied in the Indonesian context. This research also highlights aspects such as digital infrastructure, workforce skills, and government policies that support or hinder the development of Industry 5.0 in Indonesia. It is hoped that this research can provide valuable insights for policy makers and stakeholders in understanding the contribution of Industry 5.0 to the Indonesian economy and formulating appropriate strategies to encourage sustainable economic growth.